2002
DOI: 10.1111/j.1574-6968.2002.tb11190.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection of anti-hapten antibodies isolated from synthetic and semi-synthetic antibody phage display libraries expressed inEscherichia coli

Abstract: Antibody phage display libraries (Griffin and Tomlinson I) displaying antibody genes and maintained and amplified in Escherichia coli were used to isolate antibodies to the hapten target microcystin LR (1000 Da) conjugated to either bovine serum albumin or keyhole limpet haemocyanin. In competition enzyme-linked immunosorbent assay, bacterially expressed antibodies selected via the Griffin library showed at least 300 times greater sensitivity than those isolated from the Tomlinson library, for free microcystin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, modified panning strategies used to increase the likelihood of isolating high-affinity hapten binders are: 1 to gradually decrease the coating conjugate concentration during successive rounds of panning [25]; 2 to use the free hapten to elute the hapten-specific antibodies; 3 to use analogues with which the antibodies are preincubated prior to their incubation with the target hapten conjugate; 4 to perform subtractive panning, where the antibodies are incubated with the carrier protein prior to incubation with the hapten–protein conjugate [26]. Subtractive panning should remove any antibody binding to the carrier protein, but not those antibodies binding to the bridging group linking the protein and the hapten.…”
Section: Discussionmentioning
confidence: 99%
“…However, modified panning strategies used to increase the likelihood of isolating high-affinity hapten binders are: 1 to gradually decrease the coating conjugate concentration during successive rounds of panning [25]; 2 to use the free hapten to elute the hapten-specific antibodies; 3 to use analogues with which the antibodies are preincubated prior to their incubation with the target hapten conjugate; 4 to perform subtractive panning, where the antibodies are incubated with the carrier protein prior to incubation with the hapten–protein conjugate [26]. Subtractive panning should remove any antibody binding to the carrier protein, but not those antibodies binding to the bridging group linking the protein and the hapten.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that while shorter heavy-chain CDR3s tend to form planar binding sites suitable for binding large proteins, longer heavychain CDR3s are capable of forming anti-hapten binding pockets (5,36). The heavy-chain CDR3 in the Tomlinson I library is conserved at seven amino acids, while the Griffin.1 library incorporates variable heavy-chain CDR3 lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy-chain CDR3 in the Tomlinson I library is conserved at seven amino acids, while the Griffin.1 library incorporates variable heavy-chain CDR3 lengths. Panning of the Griffin.1 library against microcystin-LR conjugates enabled the isolation of a more sensitive anti-microcystin-LR clone (3A8), which was found to have 10 amino acid residues at this position (36).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, recombinant antibody libraries can be built using synthetic diversity (79) in which antibody complementarity determining region (CDR) containing gene fragments are generated with mixed-nucleotide synthesis (10). A semi-synthetic approach can also be used to further diversify native heavy and light chain genes by synthetically randomizing the CDRs (11). Disadvantages to these library types include variable biophysical properties and expression levels of heterogeneous frameworks, and stop codons in mixed-nucleotide sequences in synthetic and semi-synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%